EVALUATION OF FARMERS APPRECIATION IN REDUCING PESTICIDE BY ORGANIC FARMING PRACTICE - Indraningsih Indraningsih; Yulvian Sani; Raphaella Widiastuti (Indonesian Journal of Agricultural Science, 2005)
Vegetables and dairy milk are important commodities in Pangalengan and Lembang, West Java. However, agrochemicals are used intensively and excessively in production system. Therefore, pesticide residues and contamination commonly occurred in agricultural products and environments. The study aimed to assess farmers’ attitudes on pesticide toxicity and reducing pesticide residues in animal and food crops products, and investigate the attitude changes of farmers on pesticide use. It was an on-farm research and farmers were directly involved in the study. The attitude change was analyzed on questionnaire and interview base for over 99 respondents in Pangalengan and Lembang between 2001 and 2003. Samples of soils, weeds, cabbages and milk were collected for pesticide residue analysis. Results showed that farmers did not aware on toxicity effects of pesticides in both animal and human health. There was misinterpretation among the farmers where pesticides were regarded as drugs rather than toxic compound to increase productivity. The organochlorines/OCs (lindane and heptachlor) were common pesticide contaminants found in soils of 7.9- 11.4 ppb, but no organophospates (OPs) were detected. Both OCs and OPs were also detected in soils of Lembang at a range of 11.53-65.63 ppb and 0.6-2.6 ppb, respectively. There were pesticide residues detected in weeds collected from Pangalengan (8.93 ppb lindane, 2.05 ppb heptachlor, and 33.27 ppb chlorpyriphos methyl/CPM and Lembang (6.45 ppb lindane, 2.65 ppb endosulfan, 6.85 ppb diazinon, and 0.5 ppb CPM). Only endosulfan with least residue level (0.1 ppb) was detected in organic cabbages, whereas lindane was detected much higher (3.7 ppb) in non-organic cabbages. Pesticide residues were not detected in milk of dairy cattle fed on by-products of organic cabbages, but lindane was still present in milk of dairy cattle fed on non-organic cabbages for 7 days subsequently. The present study indicates that the organic farming practice may reduce pesticide residues in animal and agricultural products. Farmers appreciated that pesticides may cause residual effects on their products (95.2%) and affected public health and environment (92.9%). Therefore, they were willing to convert their agricultural practices to organic farming (69.1%).